Europe and Central Asia Economic Update, November 2016 : Polarization and Populism - World Bank (Washington, DC: World Bank, 2016)
These are tough times for Europe and Central Asia. The Brexit vote and the refugee crisis are testing the European Union’s internal cohesion. Continued vulnerabilities in European banking sectors are curbing the economic recovery. Russia, Eastern Europe, Central Asia, and the Caucuses are still grappling with the consequences of low oil prices, increasingly compounded by low prices of other commodities. In Turkey, social and political tensions have increased in the aftermath of the coup attempt. Moreover, geopolitical frictions in the region further complicate the challenges. These turbulent economic times coincide with political polarization and rising populism. This likely reflects anxiety about unequal opportunities and decreasing job security, while low secular growth causes more pessimism about prospects. Coping with the structural challenges outlined above and limiting the rise in populism will require policies that support adjustment to these new economic realities while minimizing the pain that such adjustments can cause.